The Significance of Mobile Applications Based Learning in Creating Awareness of Occupational Health and Safety - Aulia Nugraha, Muhamad Faisal; Roemintoyo, Roemintoyo; Djono, Djono (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
ntroduction: In this study,